A 9-aminoacridine derivative induces growth inhibition of Ehrlich ascites carcinoma cells and antinociceptive effect in mice - Mangueira, Vivianne M.; de Sousa, Tatyanna K. G.; Batista, Tatianne M.; de Abrantes, Renata A.; Moura, Ana Paula G.; Ferreira, Rafael C.; de Almeida, Reinaldo N.; Braga, Renan M.; Leite, Fagner Carvalho; Medeiros, Karina C. de P.; Cavalcanti, Misael Azevedo T.; Moura, Ricardo O.; et al. (Frontiers in Pharmacology, 2022)
Acridine compounds constitute a class of compounds with a broad spectrum of biological activities. Herein, we aimed to evaluate the toxicological, antitumor, and antinociceptive actions of n’-(6-cloro-2-metoxiacridin-9-il)-2-cianoacetohidrazide (ACS-AZ), an acridine compound with antimalarial activity. The toxicity was assessed by acute toxicity and micronucleus tests in mice, and the Ehrlich ascites carcinoma model was used to assess the antitumor action of ACS-AZ (12.5, 25, or 50 mg/kg, intraperitoneally, i.p.), as well as toxicity. The formalin and hot plate tests were used to evaluate the antinociceptive effect of ACS-AZ (50 mg/kg, i.p.). The role of the opioid system was also investigated. LD50 (lethal dose 50%) was estimated at around 500 mg/kg (i.p.), and no genotoxicity was recorded. After 7-day treatment, ACS-AZ significantly reduced tumor cell viability and peritumoral microvessels density. In addition, ACS-AZ reduced IL-1β and CCL-2 levels, while increasing TNF-α and IL-4. These findings suggest that ACS-AZ may modulate the inflammatory microenvironment to promote the antitumor effects. ACS-AZ also decreased oxidative stress and nitric oxide levels, which are crucial mediators in cancer progression. Moreover, weak toxicological effects were recorded after 7-day treatment (biochemical, hematological, and histological parameters). Concerning antinociceptive activity, ACS-AZ was effective on the hotplate test, and in both phases of the formalin test. Through pretreatment with opioid antagonists, we observed that the antinociceptive effect is mediated by the opioid pathway, especially by μ1-opioid receptors. In conclusion, ACS-AZ has low toxicity and antitumoral activity by inducing antiangiogenic, antioxidant, and immunomodulatory effects, in addition to antinociceptive properties involving the opioid system. Then, we present ACS-AZ as a promising compound in the arsenal of acridine derivatives with antitumor and antinociceptive actions.